Future of solar photovoltaic : deployment, investment, technology, grid integration and socio-economic aspects (International Renewable Energy Agency, 2019)
Reducing carbon dioxide (CO2) emissions is at the heart of the world's accelerating shift from climate-damaging fossil fuels towards clean, renewable forms of energy. The steady rise of solar photovoltaic (PV) power generation forms a vital part of this global energy transformation. In addition to fulfilling the Paris Agreement, renewables are crucial to reduce air pollution, improve health and well-being, and provide affordable energy access worldwide. This paper from the International Renewable Energy Agency (IRENA) presents options to speed up deployment and fully unlock the world's vast solar PV potential over the period until 2050. The analysis follows the REmap Case outlined in IRENA's Global Energy Transformation roadmap, which highlights ways to step up the energy transformation over the next three decades in contrast to current plans. Specifically, the paper highlights the growth needed in solar PV to achieve climate goals. It also offers insights on cost reduction, technology trends and the need to prepare electricity grids for rising shares of solar PV.